PENGEMBANGAN MODUL BERBASIS POE (PREDICT, OBSERVE, EXPLAIN) PADA KD 3.10 MATERI ASAM BASA KELAS XI SEKOLAH MENENGAH ATAS (SMA) - Sari, Rita Purnama; Erviyenni, Erviyenni; Haryati, Sri (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This research aims to determine the validity of Predict-Observe-Explain (POE) based module based on feasibility aspects of content, language, graphics and presentation. And to know the practical test module of teachers and studens. Type of development research refers to the R & D (Research and Development) using 4D model converted language 4P model. The sample of validation product validation by SMAN 5 Pekanbaru and SMA Babusalam Pekanbaru. Technique of collecting data with validation sheet given to expert validator that is lecturer and questionnaire with teacher and learner. Based on the result of the research, it can be concluded that the quality of the module based on feasibility aspects of content, language, presentation, and graphics are as follows: the contents of the module have 92.5% percentage. (valid), the language feasibility of the module has a percentage of 87.5% (valid), the feasibility of presentation of the module has 100% percentage (valid), the feasibility of module keypad has 87.5% percentage (valid), overall average validation score module KD 3.10 acid base material based on Predict Observe Explain is 97,67% and included valid category. Percentage of teacher and student respondents in SMAN 5 Pekanbaru and SMA Babusalam Pekanbaru to module KD 3.10 Predict Observe Explain material acid base. The percentage of teachers as a user response is 97.5% with very practical criteria. While the percentage of students in SMAN 5 Pekanbaru and SMA Babusalam Pekanbaru are 96.37% and 96.00% respectively with average score is 94,61% very practical criteria.Key words: Modules, POE, KD 3,10 acid bases